Pigmalione: le forme e la struttura di un mito di sublimazione (ENTHYMEMA, 2013)
This essay aims at defining pygmalionism and the  Pygmalion effect by comparing different versions of the myth, in particular the highbrow ones, i.e.  Ovid’s and  Rousseau’s, as well as analyses offered by scholars such as Maurizio Bettini, Gianpiero Rosati, Emilio Pianezzola, Charles Segal and Piero Bernardini Marzolla. This is a partial and selective overview which does not aim at completeness and exhaustiveness; the goal is to make a structural analysis of the myth by considering some variants in synchronic perspective. It will be first shown  how, from a specific moment onwards, the artist who had been able to move Olympic gods and had his love desire granted, becomes a comic figure, where he is the main object of jokes and pranks,  then we will see how George Bernard Shaw’s Pygmalion enacts the problematical shift from myth to anti-myth.